2021
DOI: 10.1021/acs.inorgchem.1c03670
|View full text |Cite
|
Sign up to set email alerts
|

Chelating the Alpha Therapy Radionuclides 225Ac3+ and 213Bi3+ with 18-Membered Macrocyclic Ligands Macrodipa and Py-Macrodipa

Abstract: The radionuclides 225Ac3+ and 213Bi3+ possess favorable physical properties for targeted alpha therapy (TAT), a therapeutic approach that leverages α radiation to treat cancers. A chelator that effectively binds and retains these radionuclides is required for this application. The development of ligands for this purpose, however, is challenging because the large ionic radii and charge-diffuse nature of these metal ions give rise to weaker metal–ligand interactions. In this study, we evaluated two 18-membered m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…Notably, py 2 -macrodipa quantitatively incorporates 225 Ac 3+ at a low concentration of 10 –5 M within 5 min, revealing it to be an efficient chelator for 225 Ac 3+ . This property is nearly on par with that of macropa, the current gold standard, which quantitatively radiolabels 225 Ac 3+ at micromolar concentration, an observation consistent with previously reported results. , By contrast, DOTA did not significantly undergo 225 Ac 3+ radiolabeling even at a millimolar concentration. Increasing the reaction time to 60 min had only a slight effect on the RCYs for py 2 -macrodipa and macropa, indicating that the radiolabeling process is nearly complete within 5 min under these mild conditions for both chelators.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, py 2 -macrodipa quantitatively incorporates 225 Ac 3+ at a low concentration of 10 –5 M within 5 min, revealing it to be an efficient chelator for 225 Ac 3+ . This property is nearly on par with that of macropa, the current gold standard, which quantitatively radiolabels 225 Ac 3+ at micromolar concentration, an observation consistent with previously reported results. , By contrast, DOTA did not significantly undergo 225 Ac 3+ radiolabeling even at a millimolar concentration. Increasing the reaction time to 60 min had only a slight effect on the RCYs for py 2 -macrodipa and macropa, indicating that the radiolabeling process is nearly complete within 5 min under these mild conditions for both chelators.…”
Section: Resultssupporting
confidence: 91%
“…Based on these improvements of macrodipa, we showed that py-macrodipa efficiently formed stable complexes with 135 La 3+ and 44 Sc 3+ , two valuable radionuclides for nuclear medicine with significantly disparate ionic radii . To further validate the potential of py-macrodipa for nuclear medicine applications, we assessed its suitability for chelating 225 Ac 3+ and 213 Bi 3+ , two therapeutically valuable α-emitters. , These studies showed that py-macrodipa is a promising candidate for 213 Bi 3+ chelation but does not form a complex of sufficient kinetic stability for 225 Ac 3+ nuclear medicine applications …”
Section: Introductionmentioning
confidence: 99%
“…Even though the pymacrodipa complex with Ac 3+ is kinetically labile and not optimal for nuclear medicine purposes, the Bi 3+ complex has remarkable kinetic stability, surpassing that of macropa. 70 This study established py-macrodipa as a promising candidate for 213 Bi 3+ chelation, representing an extension of its versatility for a wide range of metal ions.…”
Section: Stable Chelation For Both the Large And Small Metal Ions: Th...mentioning
confidence: 93%
“…On the basis of the success of py-macrodipa with 135 La 3+ and 44 Sc 3+ , we next employed this system for other non-Ln 3+ radiometals such as large α-emitting radiometals 225 Ac 3+ and 213 Bi 3+ . Despite the nearly identical ionic radii of La 3+ and Bi 3+ , 28 the Bi 3+ complex of py-macrodipa adopts asymmetric Conformation B, 70 which is normally preferred for small ions. This unexpected geometry is possibly a consequence of the stereochemical activity of the Bi 3+ 6s 2 lone pair.…”
Section: Stable Chelation For Both the Large And Small Metal Ions: Th...mentioning
confidence: 99%
“…The lack of stability is likely a product of both small ring size and the distance between the metal ion and the oxygen donor atoms of the acetic acid pendant arms [224] . To address these limitations, larger 18-membered macrocycles such as macropa [183] , crown [225] , py-macrodipa [226] , and mcp-D-click [227] have recently been introduced to chelate 225 Ac 3+ or 213 Bi 3+ with exceptionally high stability. An alternative approach has been to explore acyclic hydroxypyridinonate (HOPO) or picolinic acid chelators.…”
Section: Introductionmentioning
confidence: 99%